Cerebral venous distention associated with cardiac failure in infants. - Kuharik, M A; Edwards, M K (American Journal of Neuroradiology, 1987)
Three infants with congestive cardiac failure demonstrated dilated and hyperdense intracranial veins and sinuses on noncontrast cranial CT. Intracranial venous thrombosis and arteriovenous malformation were excluded in two infants by autopsy and in one infant by MR imaging. We believe the CT findings were secondary to an elevated central venous pressure caused by the cardiac failure. This CT pattern suggests venous congestive failure, and it should alert the clinician and radiologist to the risk of subsequent sinus thrombosis.